Sustainable Consumption: Eco-labelling and its impact on consumer behavior - evidence from a study on Polish consumer - Lucyna Witek (Institute of Economic Research (IER), 2017)
Environmental pollution has led to a growing interest in protecting the environment of various stakeholder groups, especially consumers, who in their purchasing behavior point to eco-labels. The purpose of the study is to analyze consumers attitudes towards eco-labels. The direct survey method was used. The survey was conducted from 1 December 2015 to 31 January 2016 among 390 consumers who are residents of south-eastern and southern Poland. The study conducted confirms that consumers have positive attitudes toward eco-labels, but have overall and partial knowledge of them. Almost half of respondents (48.2%) buy eco-labels, but only a small group has knowledge of various eco-labels (24.9%). The recognition of EU eco-labels is declared by 43.4% of survey participants (national eco-label - 35.1%). One may notice an inconsistency in the test participant declarations. A large group of respondents believe that manufacturers use eco-labels for sales and image purposes (61%). Only one third (32.1%) have confidence in eco-labels products. Quite a large number of respondents (43.1%) are willing to pay a higher price for such products. Almost three quarters of respondents declared that they were buying products from reliable sources but without eco-labels (76.2%). This study is a valuable contribution to research and a discussion on consumer ecological behavior, and contributes to sustainable consumption research. It creates a deeper and more detailed analysis of attitudes towards eco-labelling. It gives guidance to manufacturers and retailers, especially in consumer communication strategies. The results of the study may help to increase the effectiveness of eco-labelling. The research implies some values to society and helps to solve environmental problems.
Keywords: D12; M31; M37; Q56; 330; green product; sustainable consumption; eco-labelling; consumer; ecolabel